Aliens of the deep - Cameron, James 1954-; Quale, Steven (Walt Disney Home Entertainment ; distributed by Buena Vista Home Entertainment ; distributed in the Philippines by Viva Video, 2005)
James Cameron teams up with NASA scientists to explore the Mid-Ocean Ridge, a submerged chain of mountains that band the Earth and are home to some of the planet's most unique life forms.